Contemporary Art and National Identity: Reflections Based on the Work of the Costa Rican Artist Pedro Arrieta - Jiménez Bolaños, Jos´é Daniel (2025)
Introduction: Art and artists have played a central role in the process of symbolizing the Nation-State. Pedro Arrieta (1954-2004) belongs to a generation of Costa Rican artists who developed innovative forms of expression, in dialogue with contemporary social conflicts and a critical vision of the official narratives of national identity. Objective: This paper aims to contribute to the discussions on contemporary art and national identity, based on the analysis of the work of Pedro Arrieta, especially his art installation Símbolos Patrios. Methods: The news, chronicles, reviews and interviews published in the newspapers La República, La Nación and Semanario Universidad between 1990 and 2013 were examined along with the artist’s catalogue and other national and international works that have addressed the link between contemporary art and politics. Conclusions: Arrieta, both in his individual work and in his participation within the Bocaracá collective, was a fundamental character in the displacement of Costa Rican art at the end of the 20th century. Its consecration and institutional legitimation within the framework of the national sculpture Biennials, as well as its international projection, enhanced the dialogues and discussions on topics of his emphasis, such as national identity and the Costa Rican idiosyncrasy.